Effect of Bongi Me’e Liquid Soap Toward Staphylococcus Epidermidis - Farid Wajdi; Suhratul Aini; Fitria Aprillah Nardi; Desy Komalasari (Chemistry Education Program, the University of Mataram, 2019)
Acne or commonly referred as Acne Vulgaris is a chronic skin disease due to abnormalities of sebum production in sebaceous glands caused by Staphylococcus epidermis bacteria. Acne treatment is usually done by using antibiotics, both topical and oral like Clindamycin 1%. However, the long-term use of antibiotics might lead to resistant of Propionibacterium acne strains or immune to Clindamycin 1%. People in Bima, particulary in Wawo district have local wisdom, that is facial using Bongi Me’e which is a traditional scrubs made of rice, tamarind, and temu giring extract that officacious as antibacterial. The purpose of this study was to determine the effectiveness of Bongi Me’e liquid soap as the antibacterial against Staphylococcus epidermis. In this research, four soap formulas were formulated and tested using well diffusion method. Formula 1 (4 ml rice extract, 3 ml temu giring extract and 2 ml tamarind extract). Formula 2 ( 2 ml rice extract, 3 ml temu giring extract and 4 ml tamarind extract). Formula 3 (2 ml rice extract, 4 ml temu giring extract, and 3 ml tamarind extract). Formula 4 (4 ml rice extract, 2 ml temu giring extract, and 3 ml tamarind extract). The inhibitory zone test indicated that the highest diameter of inhibition zone obtained in the formula 1 of 29,3 mm, followed by the formula 2 of 28 mm, formula 4 of 26,6 mm, and formula 3 that has smallest inhibitory zone by 25 mm. So, the antibacterial Bongi Me’e liquid soap was effective to inhibit acne-cause bacteria Staphylococcus epidermis